2020
DOI: 10.2147/cmar.s268378
|View full text |Cite
|
Sign up to set email alerts
|

<p>MicroRNA-139 Suppresses the Tumorigenicity of Triple Negative Breast Cancer Cells by Targeting SOX8</p>

Abstract: The effects of miR-139 on the tumorigenicity of triple negative breast cancer (TNBC) and the underlying mechanisms were investigated. Methods: Normal human breast epithelial (MCF-10A) and TNBC cell lines (HCC1806 and BT549) were used for microRNA (miR)-139 overexpression, SOX8 overexpression, and knockdown studies as in vitro models of TNBC. The expression of SOX8 and miR-139 was detected by reverse transcription-polymerase chain reaction. CCK8 and clone formation assays were used to evaluate cell proliferatio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
5
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 21 publications
0
5
0
Order By: Relevance
“…MiR-205 is another negative regulator of stemness in TNBC which targets ZEB1/2 and is repressed by Notch signaling [220,221] . Dong et al [222] demonstrated miR-139 suppresses tumorigenicity in TNBC by targeting CSC factor SOX8. MiR-200c also inhibits CSC-factor ZEB2 in TNBC, repressing EMT [223] .…”
Section: Epigenetic Regulators Of Stemness In Tnbcmentioning
confidence: 99%
See 1 more Smart Citation
“…MiR-205 is another negative regulator of stemness in TNBC which targets ZEB1/2 and is repressed by Notch signaling [220,221] . Dong et al [222] demonstrated miR-139 suppresses tumorigenicity in TNBC by targeting CSC factor SOX8. MiR-200c also inhibits CSC-factor ZEB2 in TNBC, repressing EMT [223] .…”
Section: Epigenetic Regulators Of Stemness In Tnbcmentioning
confidence: 99%
“…Dong et al . [ 222 ] demonstrated miR-139 suppresses tumorigenicity in TNBC by targeting CSC factor SOX8. MiR-200c also inhibits CSC-factor ZEB2 in TNBC, repressing EMT [ 223 ] .…”
Section: Epigenetic Regulators Of Stemness In Tnbcmentioning
confidence: 99%
“…Dependent on m6A modification, KIAA1429 increases the stability of its downstream genes and thus elevates their expressions in cancers [15,24]. SOX8 is considered a detrimental prognostic factor for triple-negative breast cancer and tongue squamous cell cancer [19,34,35].…”
Section: Discussionmentioning
confidence: 99%
“…Dependent on m6A modification, KIAA1429 increases the stability of its downstream genes and thus elevates their expressions in cancers [ 15 , 24 ]. SOX8 is considered a detrimental prognostic factor for triple-negative breast cancer and tongue squamous cell cancer [ 19 , 34 , 35 ]. Additionally, several studies have highlighted the role of SOX8 in augmenting EMT and drug resistance in cancers [ 36–38 ].…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies have shown that miR-21 overexpression in breast cancer is associated with cell proliferation, progression, metastasis, and poor prognosis [ 38 , 39 ]. It has also been reported that miR-21 promotes invasion and cell proliferation by targeting programmed cell death 4 (PDCD4) [ 38 ]; miR-139 has been reported to act as a tumor suppressor in several cancer types, such as prostate cancer, endometrial cancer, and breast cancer [ 40 , 41 , 42 ]. In addition to miR-21 and miR-139, selected DE miRNAs have also been confirmed to function as one of the major components in cancer biology by other groups.…”
Section: Discussionmentioning
confidence: 99%